Thermal degradation of two different polymers bearing amide pendant groups prepared by ATRP method - Demirelli, Kadir; Kaya, Esin; Coskun, Mehmet; Bagci, Eyup (Springer, 2013)
Piperidinocarbonylmethyl methacrylate (PyCMMA) and 1-(piperidinocarbonyl) ethylmethacrylate (PyCEMA) monomers were synthesized. Polymerizations of PyCMMA and PyCEMA were carried out by atom transfer radical polymerization. The structure of monomers and polymers was characterized by H-1-NMR, C-13-NMR, and FT-IR spectroscopies. Characterization of poly(PyCMMA) and poly(PyCEMA) were carried out using differential scanning calorimetry and gel permeation chromatography. The experimental results showed that the reaction exhibited characteristics of controlled polymerization. The thermal degradation behaviors of poly(PyCEMA) and poly(PyCMMA) were studied using thermogravimetry and a single line vacuum system consisting of a degradation tube with a condenser for product collection. The poly(PyCEMA) and poly(PyCMMA) were heated from ambient temperature to 325 and 500 A degrees C, respectively. The products of degradation were collected as a cold ring fraction (CRF). The CRFs of degradation were investigated by means of IR, (HNMR)-H-1, and GC-MS. For the degradation of both polymers, the major products of CRFs are piperidinocarbonyl methanol and 1,2-dipiperidino,1-oxo ethane. The GC-MS, IR, and NMR data showed that depolymerization below 325 A degrees C to the corresponding monomer was not prominantin the thermal degradation of poly(PyCMMA). The mode of thermal degradation including formation of the major products was identified.
Keywords: ATRP; Piperidine; Synthesis; Thermal degradation